Effects of Short-Chain Fatty Acid Modulation on Potentially Diarrhea-Causing Pathogens in Yaks Through Metagenomic Sequencing - Li, Kun; Zeng, Zhibo; Liu, Juanjuan; Pei, Lulu; Wang, Yaping; Li, Aoyun; Kulyar, Muhammad Fakhar-e-Alam; Shahzad, Muhammad; Mehmood, Khalid; Li, Jiakui; Qi, Desheng (Frontiers in Cellular and Infection Microbiology, 2022)
Short-chain fatty acids (SCFA) are principal nutrient substrates of intestinal epithelial cells that regulate the epithelial barrier in yaks. Until now, metagenomics sequencing has not been reported in diarrheal yaks. Scarce information is available regarding the levels of fecal SCFA and diarrhea in yaks. So, our study aims to identify the potential pathogens that cause the emerging diarrhea and explore the potential relationship of short-chain fatty acids in this issue. We estimated diarrhea rate in yaks after collecting an equal number of fecal samples from affected animals. Metagenomics sequencing and quantitative analysis of SCFA were performed, which revealed 15%–25% and 5%–10% prevalence of diarrhea in yak’s calves and adults, respectively. Violin box plot also showed a higher degree of dispersion in gene abundance distribution of diarrheal yaks, as compared to normal yaks. We found 366,163 significant differential abundance genes in diarrheal yaks, with 141,305 upregulated and 224,858 downregulated genes compared with normal yaks via DESeq analysis. Metagenomics binning analysis indicated the higher significance of bin 33 (Bacteroidales) (p < 0.05) in diarrheal animals, while bin 10 (p < 0.0001), bin 30 (Clostridiales) (p < 0.05), bin 51 (Lactobacillales) (p < 0.05), bin 8 (Lachnospiraceae) (p < 0.05), and bin 47 (Bacteria) (p < 0.05) were significantly higher in normal yaks. At different levels, a significant difference in phylum (n = 4), class (n = 8), oder (n = 8), family (n = 16), genus (n = 17), and species (n = 30) was noticed, respectively. Compared with healthy yaks, acetic acid (p < 0.01), propionic acid (p < 0.01), butyric acid (p < 0.01), isobutyric acid (p < 0.01), isovaleric acid (p < 0.05), and caproic acid (p < 0.01) were all observed significantly at a lower rate in diarrheal yaks. In conclusion, besides the increased Staphylococcus aureus, Babesia ovata, Anaplasma phagocytophilum, Bacteroides fluxus, viruses, Klebsiella pneumonia, and inflammation-related bacteria, the decrease of SCFA caused by the imbalance of intestinal microbiota was potentially observed in diarrheal yaks.